Deep water, ancient ships : the treasure vault of the Mediterranean - Bascom, Willard (Garden City, N.Y. : Doubleday, 1976)
A Popularly written book on ships which are said to have been sunk in the deep waters of the Mediterranean Sea before the time of Christ, discussing why they sank, how to find them and methods for salvaging them.
Includes index.
Bibliography: p. [214]-216.
13 28 30 39
Keywords: Shipwrecks -- Mediterranean Sea; Shipwrecks -- Black Sea; Underwater archaeology -- Mediterranean Sea; Underwater archaeology -- Black Sea; Ships, Ancient -- Mediterranean Sea; Ships, Ancient -- Black Sea; Mediterranean region -- Antiquities